GROUP COMMUNICATION PROCESS BETWEEN MOBILE LEGEND GAME PLAYERS IN PENDEKAR ESPORTS COMMUNITY - Alicia Marissa Wirajaya Hosky; Tangguh Okta Wibowo (Lafadz Jaya Publisher, 2023)
This research highlights how mobile gaming, and in particular Mobile Legend, has evolved from mere entertainment to a professional field that generates revenue. Players, especially in e-sports teams such as Pendekar Esports, have created complex communities with symbolic interactions that influence each other and lead to cooperation to achieve victory in competition. This research uses the case study method on an Esports team, Pendekar Esports, to further research related to the communication of the interactions that are built. The results of this study increase the complexity of the communication and interaction process that takes place in the world of e-sports, proving that games are not just entertainment, but also bring out significant social and professional dynamics. This research applies symbolic interactionism theory to describe individual views of the team, changes in identity when becoming a professional player, and the impact of the team environment on players' attitudes and behaviour. The concept of 'spirit' illustrates the motivation of players to combine hobbies and income in Pendekar Esports. The concept of